Simultaneously achieving high performance of thermal stability and power consumption via doping yttrium in Sn15Sb85 thin film. (25th June 2023) - Xu, Shengqing; Wu, Weihua; Gu, Han; Zhou, Xiaochen; Zhu, Xiaoqin; Zhai, Jiwei; Song, Sannian; Song, Zhitang
Abstract: The effects of yttrium dopants on the phase change behavior and microstructure of Sn15 Sb85 films have been systematically investigated. The yttrium-doped Sn15 Sb85 film has the higher phase transition temperature, ten year data retention ability and crystallization activation energy, which represent a great improvement in thermal stability and data retention. X-ray diffraction, transmission electron microscopy and x-ray photoelectron spectroscopy reveal that the amorphous Sn and Y components restrict the grain growth and decrease the grain size. Raman mode typically associated with Sb is altered when the substance crystallized. Atomic force microscopy results show that the surface morphology of the doped films becomes smoother. T-shaped phase change storage cells based on yttrium-doped Sn15 Sb85 films exhibit the lower power consumption. The results demonstrate that the crystallization characteristics of Sn15 Sb85 film can be tuned and optimized through the yttrium dopant for the excellent performances of phase change memory.